Singapore's Foreign Policy : Coping with Vulnerability - Michael Leifer (Routledge, 2000)
The government of Singapore however has never taken the island-state's sovereign status for granted; a supposition which has been registered in a practice of foreign policy predicated on countering an innate vulnerability. That vulnerability is a function of a minuscule scale, a predominantly ethnic-Chinese identity associated with a traditional entrepot role and also a location wedged between the sea and airspace of two larger neighbours with which Singapore has never been politically at ease.